ESOPHAGEAL DIVERTICULUM AS A CAUSE OF ASPIRATION PNEUMONIA: A CASE REPORT - Szymon Antoni Kaźmierczak; Zuzanna Kaźmierczak; Natalia Sobieska; Oskar Ratajczyk (International Journal of Innovative Technologies in Social Science, 2026)
Aspiration pneumonia is a clinically significant condition that may result from unrecognized structural or functional abnormalities of the upper gastrointestinal tract. Esophageal diverticula, although often asymptomatic, can predispose patients to recurrent aspiration and serious pulmonary complications. This case report describes a 59-year-old female patient admitted with recurrent lower respiratory tract infections of unclear etiology. Comprehensive clinical assessment, laboratory testing, and radiological imaging revealed aspiration pneumonia secondary to a large esophageal diverticulum. Targeted antibiotic therapy was initiated, and the patient was referred for definitive surgical treatment. This case highlights the importance of considering gastrointestinal causes in patients with recurrent pneumonia and emphasizes the role of an interdisciplinary diagnostic approach.